AMPKα1‐LDH pathway regulates muscle stem cell self‐renewal by controlling metabolic homeostasis. (17th May 2017) - Theret, Marine; Gsaier, Linda; Schaffer, Bethany; Juban, Gaëtan; Ben Larbi, Sabrina; Weiss‐Gayet, Michèle; Bultot, Laurent; Collodet, Caterina; Foretz, Marc; Desplanches, Dominique; Sanz, Pascual; Zang, Zizhao; et al.
Abstract: Control of stem cell fate to either enter terminal differentiation versus returning to quiescence (self‐renewal) is crucial for tissue repair. Here, we showed that AMP‐activated protein kinase (AMPK), the master metabolic regulator of the cell, controls muscle stem cell (MuSC) self‐renewal. AMPKα1 −/− MuSCs displayed a high self‐renewal rate, which impairs muscle regeneration. AMPKα1 −/− MuSCs showed a Warburg‐like switch of their metabolism to higher glycolysis. We identified lactate dehydrogenase (LDH) as a new functional target of AMPKα1. LDH, which is a non‐limiting enzyme of glycolysis in differentiated cells, was tightly regulated in stem cells. In functional experiments, LDH overexpression phenocopied AMPKα1 −/− phenotype, that is shifted MuSC metabolism toward glycolysis triggering their return to quiescence, while inhibition of LDH activity rescued AMPKα1 −/− MuSC self‐renewal. Finally, providing specific nutrients (galactose/glucose) to MuSCs directly controlled their fate through the AMPKα1/LDH pathway, emphasizing the importance of metabolism in stem cell fate. Synopsis: The master regulator of cellular energy homeostasis, AMPKα1, regulates muscle regeneration by acting on lactate dehydrogenase (LDH) activity and thus the oxidative phosphorylation versus aerobic glycolysis switch that controls differentiation/self‐renewal of muscle stem cells. AMPKα1 deficiency in MuSCs strongly increases their self‐renewal, impairing tissue repair. Shifting MuSC metabolism towards glycolysis triggers self‐renewal via AMPKα1 pathway. Activation of AMPKα1 down‐regulates LDH activity and MuSC return to quiescence. High activity of LDH, a new functional target of AMPKα1, triggers MuSC self‐renewal. Abstract : The master regulator of cellular energy homeostasis, AMPKα1, regulates muscle regeneration by acting on lactate dehydrogenase (LDH) activity and thus the oxidative phosphorylation versus aerobic glycolysis switch that controls differentiation/self‐renewal of muscle stem cells.